Spectrophotometric determination of methyldopa by oxidative coupling reactions using 2,4 -dinitrophenylhydrazine reagent - Dhuha N. Ali AL-ghanam; Mohammed S. Sheet AL-Enizzi (Tikrit Journal of Pure Science, 2022)
A spectrophotometric method was developed for the determination of methyldopa. The method is based on oxidative coupling reactions with 4,2-dinitrophenylhydrazine as a reagent and in the presence of the oxidizing agent potassium periodate in the acidic medium. The product exhibits maximum absorption at 428 nm, Beer's law-subjective concentration in the range of (1-30) µg/ml, and molar absorbance of 6589,908  liters. mol-1.cm-1. The relative standard deviation was 0.418 percent, the recovery rate was 99.60 percent, and the quantitative limit attained (LOQ) was 0.261 µg/ml. The limit of detection (LOD) was 0.078µg/ml. Following the procedures of continuous changes and molar ratio, the nature of the product created from the reaction was examined, and the ratio was 2:1. (drug compound: reagent) and the value of the stable rate of stability was 8.84 x 1012 liters 2. mol-2, which indicates the good stability of this product. This method was successfully applied to estimate methyldopa in tablet form